ifo World Economic Survey February 2019 - Dorine Boumans; Johanna Garnitz (ifo World Economic Survey, 2019)
ifo World Economic Climate: ifo World Economic Climate suffers another setback - Advanced economies: Pace of economic growth in advanced economies likely to slow - Emerging and developing economies: Economic climate in emerging markets and developing economies remains subdued - Special box: Trade and foreign policy in Latin America Special topic: Energy transition around the world: is it going far enough?
Keywords: 330